Digital Empowerment in Rural Villages: Unraveling MSEs' Path to Technological Readiness and Sustainability - Susanti, Elisa; Alia, Siti; Harta, Ridho (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
This study examines the digital readiness of micro and small enterprises (MSEs) in rural Indonesia, aiming to evaluate their readiness and develop a specialized model tailored to rural challenges. Using a mixed-method approach, insights were drawn from 12 articles and 24 business participants across 11 villages, combining systematic literature reviews and in-depth interviews. The methodology focused on analyzing digital readiness dimensions such as strategy, organization, technology, finance, and market integration. Interviews with MSE owners and managers explored factors influencing digital readiness, including the macro environment, technology perceptions, motivation for adoption, social capital, and knowledge-based capabilities. Findings revealed that many rural MSEs possess a basic level of digital readiness, with some lagging due to limited technology use and owner disinterest. Addressing these challenges requires collaboration among governments, educational institutions, local communities, and the MSEs themselves. The study underscores the importance of digital readiness in enhancing the competitiveness and sustainability of rural MSEs. By developing a tailored model and addressing key challenges, rural MSEs can better leverage digital technologies to drive growth and economic development in rural areas.